Occupational Health Center as a Novel Model of Health Care Organization in Tertiary Educational Setting - Felszeghi, Sára (Frontiers in Public Health, 2022)
The activity of the Occupational Health Centre of the University of Miskolc was awarded the Best practice in Occupational Medicine by the European Network for Workplace Health Promotion in 2013. This paper presents the model, which promotes multidisciplinary health service, combined with education and research as a novel element, and will outline its impact on national and international research.